Use of the Bakri postpartum balloon in a patient with intractable pelvic floor hemorrhage: When other methods failed to stop postcesarean bleeding, physicians tried something new - Kittipat Charoenkwan (2018)
Massive pelvic floor hemorrhage is a potentially life-threatening condition associated with complicated obstetrical and gynecological procedures. Sometimes, the bleeding cannot be controlled by conventional methods. This report demonstrates the effectiveness of the Bakri balloon as a pelvic pressure pack for the control of intractable pelvic floor hemorrhage following cesarean section. © 2013 Mosby, Inc. All rights reserved.